Breaking the Cycle: Addressing Sexual Harassment in Higher Education in Bangladesh - Tabassum, Nishat; Tamanna, Farhana Jakia (CV. Literasi Indonesia, 2025)
This research examined the pervasive and deeply entrenched issue of sexual harassment within Bangladeshi universities. This research followed a qualitative research approach and was conducted on the female students of Pabna University of Science and Technology of Bangladesh. Data were collected from 20 female students through In-Depth Interviews, utilising a convenience sampling method. This study reveals that female students face both verbal and non-verbal sexual harassment on campus and outside the campus, which significantly disrupts the academic environment. Although there are legal requirements for the university to implement complaint mechanisms, institutional responses remain inconsistent, often hindered by stigma, fear of retaliation, and distrust in the justice system. Therefore, the Sexual Harassment Prevention Committee has to work effectively to punish the perpetrators and make a safe and secure environment for all.